Acute changes in kinematic and muscle activity patterns in habitually shod rearfoot strikers while running barefoot. Issue 1 (2nd January 2016) - Strauts, Janina; Vanicek, Natalie; Halaki, Mark
Abstract: The aim of this study was to observe changes in the kinematics and muscle activities when barefoot running was initially adopted by six habitually shod, recreational rearfoot striking runners. Participants ran on a treadmill shod for 5 min, completed 3 × 10-min intervals of barefoot running and then completed a final minute of shod running at a self-selected pace. Dependent variables (speed, joint angles at foot-contact, joint range of motion (ROM), mean and peak electromyography (EMG) activity) were compared across conditions using repeated measures ANOVAs. Anterior pelvic tilt and hip flexion significantly decreased during barefoot conditions at foot contact. The ROM for the trunk, pelvis, knee and ankle angles decreased during the barefoot conditions. Mean EMG activity was reduced for biceps femoris, gastrocnemius lateralis and tibialis anterior during barefoot running. The peak activity across the running cycle decreased in biceps femoris, vastus medialis, gastrocnemius medialis and tibialis anterior during barefoot running. During barefoot running, tibialis anterior activity significantly decreased during the pre-activation and initial contact phases; gastrocnemius lateralis and medialis activity significantly decreased during the push-off phase. Barefoot running caused immediate biomechanical and neuromuscular adaptations at the hip and pelvis, which persisted when the runners donned their shoes, indicating that some learning had occurred during an initial short bout of barefoot running.